Participatory planning for disaster risk reduction: learning pathways to bridge the gap between state and territory - Recharte, Jorge (2024)
This case study discusses a problem identified in the global literature: the difficulty of national states in translating their policy instruments for disaster risk reduction and climate change adaptation into effective actions at the local territorial level. We review two perspectives on the territory and modes of intervention: (i) those of government agencies within the Huascarán Biosphere Reserve in Áncash and (ii) those deployed by local organizations in the context of a disaster risk reduction project. The case study presents evidence on the potential of participatory approaches to generate information that can help identify strategies that align adaptation and risk reduction actions to local well-being objectives and productive systems. It is concluded that there is a need to develop collaborative learning spaces between state agencies and communities to improve the effectiveness of policy instruments for disaster risk reduction.